Influence of cytokines on early death and coagulopathy in newly diagnosed patients with acute promyelocytic leukemia - Zhao, Shixiang; Ge, Yuanyuan; Li, Zengzheng; Yang, Tonghua (Frontiers in Immunology, 2023)
Acute promyelocytic leukemia (APL) is a subtype of acute myeloid leukemia (AML) with a better prognosis. But early death (ED) rate remains high. APL patients are simultaneously accompanied by coagulopathy and hyperinflammation at the onset. It is not known what effects cytokines have on ED and coagulopathy in these patients. Therefore, the purposes of this study are to explore the clinical differences between APL and other types of AML, the link between cytokines and coagulopathy in newly diagnosed APL, and their roles in the ED for APL. The results indicate APL at the onset have a younger age and higher incidence of ED and DIC than other types of AML. Intracranial hemorrhage (ICH), age, and PLT count are found to be independent factors for ED in newly APL, among which ICH is the main cause of ED, accounting for 61.54% (8/13). The levels of cytokines in newly APL are generally higher than that in AML (non-APL), and those in the group of ED for APL were widely more than the control group. IL-17A and TNF-β are directly related to the ED in newly APL, especially IL-17A, which also affects ICH in these patients. Moreover, the increase of IL-17A and TNF-β cause the prolongation of PT in APL patients, which reflected the exogenous coagulation pathway. However, they have no effect on APTT prolongation and FIB reduction. Thus, it is speculated that IL-17A leads to early cerebral hemorrhage death in newly APL by inducing tissue factor (TF) overexpression to initiate exogenous coagulation and further leading to excessive depletion of clotting factors and prolongation of PT. In conclusion, compared with other types of AML, APL patients have a younger age of onset and high inflammatory state, and are more likely to develop into DIC and die early. Age, and PLT count at diagnosis are independent factors for ED of APL, especially ICH. IL-17A is confirmed to be an independent risk factor for ED and ICH of newly APL. Hence, IL-17A may serve as a predictor of ED in newly diagnosed APL patients, and controlling its expression probably reduce ED in these patients.